1988
DOI: 10.1055/s-0038-1647630
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxycoumarin Oral Anticoagulants : Pharmacokinetics-Response Relationship

Abstract: SummaryThe blood coagulating factors II and VII and prothrombin times (Thrombotest) were followed during a dosage interval (= 24 h) in patients on acenocoumarol (n = 6) and on phenprocoumon (n = 6) therapy. The patients were on stable anti-coagulation (%TT: 7-13%) for at least 6 months. The study was performed to investigate the concentration-response relationship of the 4-hydroxycoumarin-type oral anticoagulants. The three parameters were stable during the 24-h interval for patients on phenprocoumon therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 11 publications
2
25
0
1
Order By: Relevance
“…This is probably due to the higher V, values of the R-enantiomers (Tables 3 and 4). However, during therapy, blood levels range from 1 to 10 liM for warfarin (Holford, 1986) and from 60 to 600 nM for acenocoumarol (Thijssen et al, 1988). The concentration of the unbound drugs will be even lower.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to the higher V, values of the R-enantiomers (Tables 3 and 4). However, during therapy, blood levels range from 1 to 10 liM for warfarin (Holford, 1986) and from 60 to 600 nM for acenocoumarol (Thijssen et al, 1988). The concentration of the unbound drugs will be even lower.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of a difference in factor II and factor VII in therapeutically anticoagulated patients on acenocoumarol may be explained by the fact that blood was collected 12-18 h after drug intake. With the use of acenocoumarol, due to its short half-life, factor VII fluctuates and the level is lowest about 16 h after drug intake [15]. Besides, the stratified analysis was based on relatively small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…shown that this feature causes a fluctuation in the plasma levels of factor VII when acenoMechanical Prostheses. For patients with mechanical heart valves, long-term OAT is recoumarol is administered every 24 h [Thijsen et al, 1988]. commended, with an INR (international normalized ratio) between 3 and 4.5.…”
Section: Oas and Their Action Mechanismmentioning
confidence: 99%